Hindrance Stressors and Job Outcomes: The Moderating Role of Political Skills. Issue 3 (21st September 2021) - Haq, Inam Ul; Zainab, Binte; Jan, Junaid Ahmad; Anwar, Farooq; Sharif, Imran
Abstract : This research examined the indirect effects of hindrance stressors on work‐family conflict and job disengagement through emotional exhaustion, moderated by employees' political skills. Data were collected from 218 employees (64% male, 36% female) working in public and private universities in Pakistan. The findings indicated that emotional exhaustion mediates the relationship between hindrance stressors and both study outcomes (i.e., work‐family conflict and job disengagement). In addition, the indirect relationship between the employees' hindrance stressors and both study outcomes through emotional exhaustion was moderated by their political skills such that the indirect effect was weaker at higher levels of political skills.